US Monetary Policy and the Stability of Currency Pegs - Ingmar Rövekamp (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
I study the pricing of American Depositary Receipts around FOMC meetings to identify the impact of US monetary policy on managed exchange rates. ADR investors assess the domestic central bank's reluctance to maintain a currency peg regime if the costs of mimicking policy rate increases in the US are high, i.e., the current state of the domestic economy is poor. In line with currency crises models of interest rate defence, I find that positive US monetary surprises increase the breakdown probability of pegs with low real GDP growth, high fiscal deficits, high sovereign risk and a weak domestic banking sector.
Keywords: E52; 330; American Depositary Receipts; Currency Crises; Exchange Rates; FOMC Meetings; Monetary Policy